Volumen de Ventas del Comercial Agroquímicos Alvarado S. - Herrera Velasquez, Ninfa Mariuxi (2017)
In the city of Babahoyo there are numerous markets of small companies and many of them are family type, which were born thanks to the entrepreneurship of people who do not maintain any dependency relationship. Small businesses are the engine of development in this City, because they generate jobs for the population and actively contribute to the Gross Domestic Product (GDP) of the Nation. Business activity brings a dynamic between buyers and sellers, it is important that any organization of any size that has as a philosophy to add value can become the focus of real and potential customers can generate an adequate income and increase sales, otherwise the day-to-day business will decrease its trade.